An effective vortex detection approach for velocity vector field - Ho, Shen-Shyang. (2013)
Detection of vortices, which are rotating flow features, is an important task to identify, analyze, and understand flow dynamics in a fluid. For example, it can be used to accurately tag nonrigid salient rotation features from large amount of wind vectors captured by orbiting satellites for hurricane research. In this paper, we describe in detail a general vortex detection algorithm motivated by Hough transform and flow vector tree structures. The vortex detection algorithm allows one to find the exact vortex center efficiently if it is in the vector field. A special case of the algorithm has been successfully applied to cyclone annotation and tracking using QuikSCAT satellite wind measurements.